Зниження витрат палива тепловозними двигунами під час сезонної експлуатації - Жалкін, Д. (Видавництво Національного університету “Львівська політехніка”, 2004)
The considered technique of régulation of a corner of an advancing of submission of fuel locomotives diesel engines, which based on principles of fuzzy logic also allows to lower specifie expenses of fuel during operation of diesel engines in different seasons of year.
Keywords: 629.4.083; 621.014.24